Aloe Vera: Potential to Reduce Fasting Blood Sugar Levels in Prediabetes - Budiastutik, Indah; Ningsih, Novia Surya (JURNAL INFO KESEHATAN, 2023)
Prediabetes is a continuous spectrum of developmental stages before a person is diagnosed with diabetes mellitus. Considering the long-term effects of pharmacological treatment, other natural-based methods are needed. The purpose of this study was to analyze the effect of Aloe Vera Juice on the reduction of fasting blood glucose levels in patients with prediabetes in Pontianak City. A pre and post-test design study was conducted between March and July 2021 at Alianyang Public Health Center. A total of 12 subjects were identified as prediabetic at the beginning of the study through screening involved in this study. The included subjects were asked to consume 175 ml of Aloe Vera Juice for 15 consecutive days and measured their fasting blood glucose (FBG) levels on the 16th day. A paired t-test was performed to determine the difference in FBG levels before and after the treatment. Present findings revealed that the mean FBG level before intervention was 107.4 mg / dL and 92.1 mg/dL after the intervention. A statistically different FBG reduction significance was found between groups (p<0.001). Consuming Aloe vera juice regularly for 15 days has proven to lower FBG levels among prediabetics. Future studies with better adherence monitor and larger sample sizes might have resulted in better determination of the intervention's effect.